Who speaks for Margaret Garner? - Reinhardt, Mark (University of Minnesota Press, 2010)
In January 1856, Margaret Garner and her family were at the center of one of the most dramatic and intensely contested fugitive slave cases in the nation's history. Just hours after escaping slavery in Kentucky and taking refuge in a home in Cincinnati, the Garners were cornered by authorities. As the captors sought to enter the house, Garner killed her two-and-a-half-year-old daughter, Mary. Reports suggested that she had tried to kill her three other children, too.